Influencia de la satisfaccion laboral en el clima organizacional de los trabajadores de la empresa rvr agro e.i.r.l. fundo luzmila de ica en el año 2013 - Rumay Silvestre, Lorena Raquel (2014)
The organizational climate is a major issue today for most companies, which seek continuous improvement of the environment of your organization in order to achieve an improvement in productivity, without losing sight of the human resource. This research is descriptive, was held at the company RVR AGRO city of Ica, during the months of May to December 2013, with the aim of knowing how job satisfaction affects the organizational climate of workers of agricultural enterprise. The research involves a systematic and detailed study of job satisfaction indicators, as well as organizational climate of workers, using for that the ethnographic, inductive - deductive method and the statistical method; while observing techniques, structured interview and questionnaire. For this investigation was taken as 20 workers shows the area of human resources, in the form of employees. He emphasized indicators of self, including labor relations and working conditions on job satisfaction; regarding the organizational climate was reasserted in motivation, communication and commitment to the work before concluding in the degree of influence of the first variable on the second variable and then arrive at conclusions and recommendations that could contribute to the research study.